CONCERNING AMERICAN LEGAL SYSTEM HISTORY FORMATION - Пильгун, Наталія Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Objective: this paper describes an individual decision of the Supreme Court of the United States, indicated the difference between federal law and law of States. It is proved that the Act takes effect and stability when he is confirmed by the judicial practice and positive court interpretation. Research methods: the historical method, comparative-law. Results: that the Supreme Court might retreat from its decisions or annul them. Discussion: the Supreme Court quite flexible approaches to the interpretation of the Constitution. But this flexibility is not inherent to the Court concerning the interpretation of constitutions of the States and their laws. Consequently: a) the American judiciary has three basic principles of activity: it acts as an arbitrator in disputed matters; it makes decisions not from general but only from concrete cases; it acts only in the event of a litigation being instituted; b) judicial supervision of compliance with the laws of the constitution of the country is carried out in the United States decentralized by courts of general jurisdiction; c) courts, as a rule, resort to fairly flexible methods of interpretation; they pay attention to ignoring the Constitution itself, but its principles; d) in most cases federal constitutional rights are protected by federal courts. The court, in turn, will consider the case where there is a harm caused and a causal link between it and the claim for compensation; e) courts in general affairs may exercise control over the activities of legislative and executive branches of power, both at state and federal level. If the case is before the federal court, in this case the federal authorities lose the right of inviolability; h) any natural or legal person in the United States has the right to contest the validity of any law in a court of law; g) the court of first instance in the federal judicial system is the district court and appeal to the district court can be appealed to the federal court of appeals.